Pola Asuh Orang Tua dalam Pembentukan Karakter Peserta Didik - Saleh, Sirajuddin; Arhas, Sitti Hardiyanti; Nur, Hasruddin (Phinisi Integration Review, 2021)
This study aims to determine: 1) Overview of parenting patterns and the formation of students' character; 2) The influence of parenting patterns on the formation of the character of students. This study uses a quantitative approach with the type of associative research. This study highlights two variables, namely parenting patterns (variable X), and the formation of students' character (variable Y). The population is 267 teachers. While the research sample as much as 50% of the total population (134 people) were taken using proportional random sampling technique. Data were collected using questionnaire, observation, and documentation techniques. Data were analyzed using descriptive statistics and inferential statistics. The results showed that: 1) The parenting pattern of the parents was in the moderate category. 2) The formation of the character of students is included in the medium category; 3) There is a positive and significant influence between parenting patterns on the formation of students' character.